Assessment and professional identity of teachers. Broken mirrors Game? (Andamios, Revista de Investigación Social, 2015)
The goal of this research study has been to analyze the politics involved in teachers’ assessment within the professional identity of teachers. Professional identity is defined as the concept of Yes in relationship to work and as the result of a personal, social and contextual construction with deep influence in the application and acceptance to innovation. Through interviews, we have gathered the narrations of two assessed teachers. Under the content analysis technique we have qualified and quantified category and subcategory relationships. Results identify the appreciations developed around the Assessment System and the effects experimented around identity; they also allow a discussion about the appropriateness and the commitment which this implies to teachers.
Keywords: Table dance; erotic dancers; performativity; striptease; institutional deficit; women